2018
DOI: 10.1093/mnras/sty2288
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological simulations of black hole growth II: how (in)significant are merger events for fuelling nuclear activity?

Abstract: Which mechanism(s) are mainly driving nuclear activity in the centres of galaxies is a major unsettled question. In this study, we investigate the statistical relevance of galaxy mergers for fuelling gas onto the central few kpc of a galaxy, potentially resulting in an active galactic nucleus (AGN). To robustly address that, we employ large-scale cosmological hydrodynamic simulations from the Magneticum Pathfinder set, including models for BH accretion and AGN feedback. Our simulations predict that for luminou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 132 publications
7
46
2
Order By: Relevance
“…However, by these times merging systems are now so rare that their (albeit enhanced) contribution is still not highly significant, and isolated galaxies remain the dominant source of BH accretion at lower redshifts. The conclusion of mergers never being statistically relevant fuelling mechanisms for BHs is consistent with the results from the Magneticum Pathfinder simulation, who performed a similar analysis to this study in the high-mass regime (M * ≥ 10 11 M , Steinborn et al 2018). However we emphasise that if we were to of restricted our study to just the high-mass regime (M * ≥ 10 11 M ) as they did, we would not of found the same result (see Figure 4).…”
Section: Is the Enhancement Of Bh Activity During Major Mergers Imporsupporting
confidence: 89%
See 1 more Smart Citation
“…However, by these times merging systems are now so rare that their (albeit enhanced) contribution is still not highly significant, and isolated galaxies remain the dominant source of BH accretion at lower redshifts. The conclusion of mergers never being statistically relevant fuelling mechanisms for BHs is consistent with the results from the Magneticum Pathfinder simulation, who performed a similar analysis to this study in the high-mass regime (M * ≥ 10 11 M , Steinborn et al 2018). However we emphasise that if we were to of restricted our study to just the high-mass regime (M * ≥ 10 11 M ) as they did, we would not of found the same result (see Figure 4).…”
Section: Is the Enhancement Of Bh Activity During Major Mergers Imporsupporting
confidence: 89%
“…Hydrodynamical simulations of merging systems have provided compelling theoretical evidence for a link between BH activity and galaxy interactions (e.g., Dubois et al 2015;Pontzen et al 2017), yet the global significance of the merging process for boosting BH activity within a full cosmological context remains largely unknown. Steinborn et al (2018) investigated the role of galaxy mergers as driving mechanisms for BH activity in the high mass regime (M * ≥ 10 11 M ) using the cosmological hydrodynamical Magneticum Pathfinder simulations. They argue, that whilst the merger fractions of AGN hosts can be up to three times higher than those of inactive galaxies, the role of merg-ers in high-mass galaxies are not statistically relevant for BH fuelling.…”
Section: Agn Luminositymentioning
confidence: 99%
“…The hydrodynamical simulation Horizon-AGN found that only ∼ 35 per cent of black hole mass in local massive galaxies is directly attributable to merging, with the majority of black hole growth instead growing via secular processes (Martin et al 2018). The Magneticum Pathfinder Simulation also found that merger events are not the dominant fuelling mechanism for black holes in z = 0-2, with merger fractions less than 20 per cent, except for very luminous quasars at z 2 (Steinborn et al 2018).…”
Section: Black Hole Growth Mechanismsmentioning
confidence: 99%
“…Mergers are associated with AGN in the EAGLE cosmological simulations, with a more compelling link at low-redshift, perhaps because gas is less readily available at late times (McAlpine et al 2018). Yet analyzing the Magneticum pathfinder simulations, Steinborn et al (2018) find that mergers only play a minor role in triggering AGN. In these simulations, the association of the most luminous AGN with mergers can to some extent be explained by the fact that more massive galaxies are inherently more likely to be in merging systems.…”
Section: Introductionmentioning
confidence: 97%